Sustainable Tourism Development Strategy of Apparalang Beach in Strengthening Tourism Competitiveness in Bulukumba Regency - Nasaruddin Nasaruddin; Shree Sharman (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2025)
Purpose of the study: This study aims to analyze and formulate sustainable tourism development strategies for Apparalang Beach in Bulukumba Regency to strengthen tourism competitiveness through the identification of tourism potential, infrastructure conditions, community participation, and environmental sustainability factors affecting destination development. Methodology: This study employed a descriptive qualitative case study approach using SWOT analysis. Data were collected through field observation, semi-structured interviews, documentation, and literature review. Research instruments included observation sheets, interview guidelines, field notes, cameras, and audio recorders. Data analysis used the Miles and Huberman interactive analysis model consisting of data reduction, data display, and conclusion drawing. Main Findings: The findings revealed that Apparalang Beach possesses strong tourism potential due to its unique coral cliff landscapes, marine scenery, and increasing tourism popularity. However, tourism development remains constrained by limited infrastructure, inadequate facilities, weak tourism management, and insufficient community participation. SWOT analysis indicated that tourism competitiveness can be improved through infrastructure development, digital tourism promotion, community empowerment, environmental conservation, and integrated stakeholder collaboration. Novelty/Originality of this study: This study provides a comprehensive SWOT-based sustainable tourism development framework integrating tourism potential, infrastructure conditions, community participation, environmental sustainability, and destination competitiveness simultaneously. The study advances tourism development research by offering integrated strategic recommendations for coastal tourism management and sustainable destination competitiveness in regional tourism contexts.